Bureaucratic Reform through Public Policy Implementing Quality Dimensions in Integrated Licensing Services - Sulila, Ismet; Ilato , Rosman; Santoso, Ivan Rahmat (Universitas Medan Area, 2024)
The bureaucratic reform of the licensing service sector in Gorontalo City was followed up by Regional Regulation Number 14 of 2006 concerning the establishment of a one-stop integrated service unit. However, the integrated service unit has not been able to provide quality services as expected. Therefore, this research is very important to provide corrections and improvements to publicly accessible licensing services. The scope of the study on the two services has reviewed the procedures carried out in the two selected services from the beginning until the licensing documents were issued. The research method used is a qualitative descriptive method through an in-depth and comprehensive study of the series of licensing services. The results showed that 1) there are differences in the application of public service dimensions in environmental permit services and building permits. 2) several factors determine the success of licensing services, namely internal factors and external factors. Internal factors include general management patterns of the organization and the provision of supporting facilities, as well as human resource development. External factors include service patterns, service provision procedures, and service distribution patterns, as well as service delivery patterns. This research provides positive benefits in the efforts of local governments to innovate public licensing services. The practical implications of the research results encourage the organization of regional equipment to meet the facility standards needed to provide quality public services.